1997
DOI: 10.1159/000119348
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Conventional and Neural Network Classifiers for Rat Sleep-Wake Stage Discrimination

Abstract: This article describes an approach to selecting the most efficient classifier for rat sleep staging (waking, REM sleep and NREM sleep) discrimination. Three conventional (bayesian, linear, and euclidean) and two neural network (multilayer perceptrons integrating or not integrating contextual information) classifiers were compared. For each classifier, performances were presented in the form of a statistical concordance matrix comparing classifier results versus human expert results on 6 24-hour records (1 reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…one cannot expect a computer to agree with two human scorers who disagree." In other words, the best one can reasonably expect is for the computer-human agreement to approach inter-rater agreement (Gottesmann et al, 1977), which is generally reported to be within the range 85-95% in rat sleep scoring (Crisler et al, 2008;Louis et al, 2004;Neckelmann et al, 1994;Robert et al, 1997;Ruigt et al, 1989b). This problem was highlighted in the present study when two raters were instructed to rate their scores as "high confidence" or "equivocal".…”
Section: Variablementioning
confidence: 73%
“…one cannot expect a computer to agree with two human scorers who disagree." In other words, the best one can reasonably expect is for the computer-human agreement to approach inter-rater agreement (Gottesmann et al, 1977), which is generally reported to be within the range 85-95% in rat sleep scoring (Crisler et al, 2008;Louis et al, 2004;Neckelmann et al, 1994;Robert et al, 1997;Ruigt et al, 1989b). This problem was highlighted in the present study when two raters were instructed to rate their scores as "high confidence" or "equivocal".…”
Section: Variablementioning
confidence: 73%
“…A postprocessing procedure based on logical rules was also used to enhance PS discrimination. Further details concerning the EEG recording technique and the neural network classifier developed can be found in [14][15][16].…”
Section: Recording and Detection Of Vigilance Statesmentioning
confidence: 99%
“…These results can be explained by the fact that the neural network is not sensitive to the distributions of the data; transformations have no effect on its ability to separate space into subspaces [26]. But, the effect of the transformation leads to an improvement of the speed of convergence for the optimization of the backpropagation during the learning process explained by a better homogeneity in the distribution of the weights and features in the input layer.…”
Section: Results With Transformed Datamentioning
confidence: 99%